Denial-of-service attack resilient control for cyber physical microgrid system - Kumar V.; Mohanty S.R. (My University, 2025)
In a microgrid network system, cyber resiliency is a prerequisite for the smooth operation under cyber threats. Denial-of-service (DOS) in microgrid-based network system has high probable cyber threat where system stability is challenged by the interruption in the communication on control signal to actuator or on the measurement of sensor data to the controller. In this chapter, input to state stability (ISS) of closed loop microgrid system is preserved by characterizing the DOS duration and frequency. ISS of the microgrid system is achieved under DOS through the determination of adequate arrangement in transmission triggering. The event trigger analysis with suitable inequality is presented both in absence and presence of DOS attack to make the controller design practically possible for the secondary voltage-frequency regulation in an autonomous AC microgrid. The law for updated control propagation is determined by the sliding mode control analysis. Lyapunov function is used to analyze the stability of microgrid system under sequence of DOS attack. The DOS-based cyber resiliency of proposed scheme is verified in MATLAB/Simulink environment. © 2022 Elsevier Inc. All rights reserved.